INDONESIAN CONSTITUTIONAL COURT’S DECISION NO. 97/PUU-XIV/2016: A CHANCE TO ENCOURAGE RECONCILIATION BETWEEN “AGAMA” AND “KEPERCAYAAN” - Asep Sandi Ruswanda (UIN Sunan Kalijaga Yogyakarta, 2020)
AbstractThis paper discussed the Constitutional Court’s decision in 2017 as a chance to encourage reconciliation of “agama” and “kepercayaan.” This paper collects responses from religious organizations through statements on the internet such as online media, the organization’s official website, or even official social media. The data is then classified based on religious affiliation and their attitude towards the Constitutional Court’s decision in 2017. On 7 November 2017, the Constitutional Court granted a judicial review of Law No. 23/2006 amended by Law No. 24 of 2013 concerning Civic Administration (UU Adminduk). This law is very significant for the group of “kepercayaan.” However, the group of “agama” has not yet fully accepted the group of “kepercayaan.” So, there needs to be reconciliation between groups of “agama” and “kepercayaan” after the decision of the Constitutional Court in 2017. By looking at the importance of the decision, it is also truly an opportunity to stop discrimination and social stigma against followers of “kepercayaan.” This paper concluded that the decision of the Constitutional Court in 2017 was an opportunity to encourage reconciliation between “agama” and “kepercayaan.”Keywords: Constitutional Court’s decision, agama, kepercayaan, reconciliation